Impact of concomitant methotrexate on disease activity in patients with rheumatoid arthritis tapering abatacept: results from KOBIO registry - Park, Jun Won; Kim, Ju Yeon; Kim, Min Jung; Lim, Yoo Kyoung; Kim, Hyoun-Ah; Kim, Jin Hyun; Shin, Kichul (Frontiers in Medicine, 2024)
Objectives: Tapering biologic agents can be considered for patients with stable disease activity in rheumatoid arthritis (RA). However, the specific strategy for abatacept is uncertain. This study aimed to examine the impact of tapering abatacept on disease activity in RA patients and assess the potential influence of concomitant methotrexate (MTX) treatment.Methods: Using data from the KOBIO registry, we included 505 1-year intervals from 176 patients with RA that initiated abatacept with concomitant MTX at baseline. The intervals were divided into two groups based on the dose quotient (DQ) of abatacept during each period (i.e., the tapering group (DQ <1) and control group (DQ =1)). The primary outcome was achieving DAS28-remission at 1-year intervals. Marginal structural models (MSM) were used to minimize confounding caused by an imbalance in time-varying variables.Abatacept was tapered at 146 (28.9%) intervals, and the mean DQ was 0.68. DAS28remission was achieved in 207 (41.8%) intervals. Tapering abatacept did not affect the odds of achieving DAS28-remission compared with the control group (OR 1.04 [0.67-1.62]). The odds remained unaffected in the subgroup that continued MTX (OR 1.42 [0.88-2.30]) but not in the subgroup that discontinued MTX ). The effects of interaction between tapering abatacept and concomitant MTX use on DAS28 and patient's functional status showed consistent results. The incidence of adverse events within a 1-year interval was comparable between the two groups.Withdrawal of MTX while tapering abatacept may compromise meeting the treatment goal for patients with RA.